2011
DOI: 10.1371/journal.pone.0019527
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cytochrome P450 and ABCB1 Genetic Variability on Methadone Pharmacokinetics, Dose Requirements, and Response

Abstract: Although the efficacy of methadone maintenance treatment (MMT) in opioid dependence disorder has been well established, the influence of methadone pharmacokinetics in dose requirement and clinical outcome remains controversial. The aim of this study is to analyze methadone dosage in responder and nonresponder patients considering pharmacogenetic and pharmacokinetic factors that may contribute to dosage adequacy. Opioid dependence patients (meeting Diagnostic and Statistical Manual of Mental Disorders, [4th Edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
121
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 77 publications
8
121
0
Order By: Relevance
“…These findings are in line with previous observations showing that pharmacokinetic factors play a marginal role for the success of methadone maintenance therapy [27, 28]. Furthermore, changes in daily methadone doses are partially associated with improved patient satisfaction in large methadone treatment facilities [29, 30].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with previous observations showing that pharmacokinetic factors play a marginal role for the success of methadone maintenance therapy [27, 28]. Furthermore, changes in daily methadone doses are partially associated with improved patient satisfaction in large methadone treatment facilities [29, 30].…”
Section: Discussionsupporting
confidence: 90%
“…As the responders had higher plasma levels of both S-and R-methadone concentration-to-dose ratios than the non-responders, it suggested that the cigarette smoking may be a physiological compensation for the low efficacy of methadone treatment. Similarly, Fonseca et al 50 have reported the non-responders smoked more cigarettes per day than responders in a Spanish MMT program.…”
Section: Discussionmentioning
confidence: 77%
“…The interactions between CYP2C19 and CYP2B6 or CYP3A4 did not show significant associations with methadone dose (data not shown), or its dose corrected plasma R-methadone or R-EDDP concentrations both in all patients and in urine opiate test negative patients (Supplementary Tables S4 and S5). As the dose of methadone may be determined by multiple genes (Fonseca et al, 2011;Hung et al, 2011), our current results indicate that the CYP2C19 GD may play a role in the N, allelic number for SNP s and subject number for gene dose; P value, permutation test p value for SNP and Kendall's coefficient of rank correlation for gene dose; (P value): p value after removing 10 subjects who had had co-medications that influence the CYP2C19 enzymatic activity (permutation test for SNP and Kendall's coefficient of rank correlation p-value for gene dose); SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%